Life cycle assessment of biosyngas from a multifunctional biomass gasification plant in Sweden - Hedbom , Héloise; Lundh, Petter (My University, 2024)
The need to increase the use of renewable energy to meet the growing energy demand and minimize the reliance on fossil fuels is evident. One renewable technology option is bioenergy due to its availability and resemblance to fossil energy carriers. This study aimed to investigate the environmental impacts of a biomass gasification plant by conducting a life cycle assessment (LCA) from cradle to grave, including multiple impact categories and comparing the results to fossil alternatives. An LCA of Meva Energy´s gasification technology that produces biosyngas was conducted with three allocation scenarios. The scenarios consider mass allocation, energy allocation, as well as one scenario where all environmental impact was allocated to the biosyngas production and the carbon sequestration effect of the produced biochar was included. The gasification system was divided into five sections: (i) the production of the plant components phase, (ii) the construction phase, (iii) the gasification phase, (iv) the use phase and (v) the end-of-life phase. The results showed that the gasification phase and use phase are the primary contributors to all impact categories, while the production of plant components phase, construction phase and end-of-life phase were shown to have negligible impacts. In terms of climate change, the biomass feedstock (wood pellets) in the gasification phase had the largest impact. The total results regarding climate change of the life cycle varied notably depending on the allocation approach applied, with a range from about 23 g CO2-eq/kWh for the mass allocation scenario to -6 g CO2-eq/kWh for the carbon sequestration scenario. Furthermore, the results varied also based on secondary material allocation and the classification of products as either waste or by-products. For example, when the sawdust used to produce wood pellets was treated as a waste stream and the emissions started upon the collection of the sawdust, the environmental impact was reduced. Moreover, considering the produced tar as a by-product rather than a waste stream had a lower but notable influence on the results, especially in the energy allocation scenario. The findings of this study highlight that energy produced by Meva Energy’s gasification technology can contribute to a climate positive impact, assuming that the application of the biochar equates a negative emission. The study also shows that the thermal energy produced by this gasification of biomass has lower climate-change impacts than the fossil alternative (liquid petroleum gas).
Keywords: Biochar; Biosyngas; Gasification; Life cycle assessment (LCA); Climate change